The effect of administration of siamese catfish (pangasius hypophthalmus) extract on fibroblast cells after tooth extraction in wistar rats - Veny Larasati; Trisnawaty; Angelina N. Ricardo (Journal of Dentomaxillofacial Science, 2022)
Objective: The study aimed to determine the effect of administration of Siamese catfish extract orally on the number of fibroblast cells in wound healing after tooth extraction of Wistar rats. Material and Methods: This research was a true experimental laboratory with posttest only control group design. 24 male Wistar rat were divided into 6 groups. After the mandibular left incisor was extracted, rats in groups 1, 2, and 3 were given Siamese catfish extract and groups 4, 5, and 6 were given aquadest orally once a day. Groups 1 and 4 were treated for 3 days, groups 2 and 5 were treated for 5 days, and groups 3 and 6 were treated for 7 days, then the rats were euthanized and made histological preparations. Fibroblast cells were calculated using Image Raster software and analyzed using One Ways ANOVA and Post Hoc LSD tests. Results: The number of fibroblast cells increased on the 5th day and reached its peak on the 7th day. ANOVA test showed a significant difference in the mean of fibroblast number between the treatment and control groups (p<0,05). Conclusion: Administration of Siamese catfish extract orally can increase the number of fibroblast cells in wound healing after tooth extraction of Wistar rats.